Separation of oil-in-water emulsion using sawdust, bentonite and calcium hydroxide [electronic resource] - Iyad Eldin Mohamed Khair Osman Elfadil, author (2014)
Project Paper (Sarjana Muda Kejuruteraan (Petroleum)) - Universiti Teknologi Malaysia, 2014